2009
DOI: 10.1080/13550280902758973
|View full text |Cite
|
Sign up to set email alerts
|

Lithium therapy for human immunodeficiency virus type 1–associated neurocognitive impairment

Abstract: Objective-To assess lithium safety and tolerability and to explore its impact on cognition, function and neuroimaging biomarkers in HIV infected subjects with cognitive impairment.Methods-Fifteen cognitively impaired HIV infected subjects were enrolled in this 10-week openlabel study of lithium 300 mg twice daily. Neuroimaging was performed at baseline, and following 10 weeks of treatment and included magnetic resonance spectroscopy (MRS), diffusion tensor imaging (DTI), and functional MRI (fMRI).Results-Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 44 publications
(50 reference statements)
3
52
0
Order By: Relevance
“…This is consistent with recent studies showing that aberrant activation of the CDK5 7,36 and GSK3␤ 7,[33][34][35]58 signaling pathways contribute to the neurodegenerative pathology in patients with HIV-associated neurocognitive impairment. Although a previous study focused on the role of p35 and CDK5 activation via the N-methyl-D-aspartate receptor (NMDAR), 36 the present study investigated the contribution of abnormal activation of this pathway to tau hyperphosphorylation in patients with HIVE.…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with recent studies showing that aberrant activation of the CDK5 7,36 and GSK3␤ 7,[33][34][35]58 signaling pathways contribute to the neurodegenerative pathology in patients with HIV-associated neurocognitive impairment. Although a previous study focused on the role of p35 and CDK5 activation via the N-methyl-D-aspartate receptor (NMDAR), 36 the present study investigated the contribution of abnormal activation of this pathway to tau hyperphosphorylation in patients with HIVE.…”
Section: Discussionsupporting
confidence: 81%
“…In HIV, human and animal models have shown decreased levels of cerebral Glx Ratai et al, 2009;Chang et al, 1997), including patients with progressive multifocal leukoencephalopathy. Another study showed decreased frontal Glx concentrations, along with increased white matter integrity on diffusion tensor imaging among patients treated with lithium for HIV-associated cognitive impairment (Schifitto et al, 2009b). Accordingly, although alteration of cerebral Glx level appears to be common in brain disorders, whether increased or decreased levels are observed seems to depend on the nature of the underlying disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Trials on rivastigmine failed to show benefit in terms of cognitive performance, but there were some secondary improvements in processing speed and executive function. To date, the therapeutic options for HAND appear limited to none [27,[30][31][32] .…”
Section: Updates In Human Immunodeficiency Virusassociated Cognitive mentioning
confidence: 99%